(untitled) (Revista de Estudos Sociais, 2021)
The impact of overweight on the consumption of energy and the impact of energy consumption on overweight was analysed for Latin America and Caribbean Countries for the period from 1975 to 2016. The Quantile via Moments econometric technique was used to assesses the role of energy consumption on mean body mass index of man and woman, controlling for the effects of global, economic and social globalisation, as well as Gross Domestic Product (GDP), urbanisation and carbon dioxide (CO2) emissions. Results point out by one hand, that as we go up in the quantiles the contribution to excess weight decreases for the variables economic globalisation, urbanisation, and energy consumption, and increases for social globalisation and CO2 emissions. On the other hand, the rise of GDP contributes to the downward overweight of women, but as we go up in the quantiles, the contribution fades away. The effect of GDP is statistically insignificant as a driver of man overweight. An additional model estimation to apprise if overweight impacts energy consumption, confirms that as overweight raises the energy consumption rises too. As we go up in the quantiles, it increases the intensity of the impact. Economic policymakers should limit the adverse effects of globalisation counteracting unhealthy food consumption habits imported from abroad. Particular attention should be put in given people access to green areas in poor urban areas. Curbing energy consumption and CO2 emissions contribute to decreasing the epidemic of overweight. Fortunately, economic growth helps to solve the problem of overweight.